OPTIMAL MOISTURE OF SOIL SAMPLES FOR SEED GERMINATION AND GROWTH OF SEEDLINGS IN CLOSED CONTAINERS - K. R. Uteulin; O. A. Agapov; K. Z. Zambakin; Y. T. Martirosyan (Scientific Journal of Pedagogy and Economics, 2019)
The purpose of the research is to determine optimum moisture content of soil samples in closed, transparent containers for seed germination and seedling growth of wild-growing wormwood – artemisia effusus (Artemisia diffusa), wild-growing type of cereal – comb-shaped wheat grass (Agropyron pectiniforme), cultured cereal – soft wheat (Tríticum aestivum), variety Saratovskaya-29. Tested soil samples with humidity of 20%, 40% and 60%. It is established that in a closed container (5 liters) soil moisture in the range of 40% - 60% provides the best seed germination and the growth of seedlings of the used plant species. In tested closed containers, soil moisture of 40% should be used, with relatively short period of plants research (30 days). With a longer period of research, it is possible to use soil with moisture content of up to 60%, because with time, the excess water is absorbed by growing plants. The method of closed containers find use for studies of influence of toxic, volatile, gaseous substances on the growth and development of plants in laboratory conditions. The results of this work will be used in modeling the ecosystem of Central Kazakhstan in connection with environmental pollution of volatile, highly toxic components of rocket-engine propellant, resulting from activities of Baikonur space-launch complex.